Resilience to shocks of micro, small, and medium-sized enterprises in Fiji - William Greenland; Russell Toth (Asian Development Bank (ADB), 2025)
This paper examines the resilience of micro, small, and medium-sized enterprises (MSMEs) in Fiji against the economic impacts of major shocks including the coronavirus disease (COVID-19) pandemic and climate-related hazards, using a survey of 2,400 MSMEs from early 2023. The analysis focuses on the effectiveness of government concessional loans in aiding pandemic recovery and evaluates MSMEs' strategies for climate resilience. Findings indicate that while government support has been pivotal in mitigating pandemic-related economic downturns, its effectiveness is varied, highlighting the necessity of accessible and targeted financial support. Furthermore, experiences with natural hazards significantly influence MSMEs' future resilience strategies, with a notable preference for self-funding recovery efforts among MSMEs that had experienced a significant climate-related disaster. The study underscores the importance of integrating immediate financial support with long-term climate adaptation strategies for MSMEs, offering insights for policy formulation aimed at enhancing economic resilience in emerging markets in the Pacific and beyond.
Keywords: Q54; L53; O56; 330; micro; small; and medium-sized enterprises; COVID-19 pandemic; concessional loans; climate resilience; Fiji